THE DEVELOPMENT OF THE COMPUTER-AIDED DESIGN SYSTEM FOR PRODUCTION PROCESSES OF COMPONENT PART MACHINING FOR SINGLE-PIECE PRODUCTION AND REPAIR CONDITIONS - Zhetessova, Gulnara; Yurchenko, Vasiliy; Nikonova, Tatyana; Zharkevich, Olga (Journal of Applied Engineering Science, 2019)
The given article provides material on the development of the CADS applied for production processes of component part machining for single-piece production and repair conditions. The article describes technique is used to organize a data flow and to cut off those methods of machining which cannot be applied under these conditions of machining. This research uses graph theory. The article describes the developed algorithm for machining planning of details. A mathematical model of transitions in the technological process for the processing of parts has been obtained. The developed design CADS reduces the number of errors in the development of production processes. The article describes database for machining planning. In order to form input data, knowledge of production processes of analogous machine parts or products production is not required. Thus developed models of system determines of machine-part production stages. This system gives schemes of its basing, a set of bases and an order of their preparation and  forming of schemes of technological dimensional chains. This system counts and recounts interoperational dimensions. Developed models and system allows to increase amount of output information to the level of operational flow charts. The designed system gives the chance of its use in modern multiproduct. This system is universal, multifunctional.
Keywords: computer modeling; technological process; computer-aided design; mechanical engineering